Noncommutative extensions of elliptic integrable Euler–Arnold tops and Painlevé VI equation. (8th September 2016) - Levin, A; Olshanetsky, M; Zotov, A
Abstract: In this paper we suggest generalizations of elliptic integrable tops to matrix-valued variables. Our consideration is based on the R -matrix description which provides Lax pairs in terms of quantum and classical R -matrices. First, we prove that for relativistic (and non-relativistic) tops, such Lax pairs with spectral parameters follow from the associative Yang–Baxter equation and its degenerations. Then we proceed to matrix extensions of the models and find out that some additional constraints are required for their construction. We describe a matrix version of the Z 2 reduced elliptic top and verify that the latter constraints are fulfilled in this case. The construction of matrix extensions is naturally generalized to the monodromy preserving equation. In this way we get matrix extensions of the Painlevé VI equation and its multidimensional analogues written in the form of non-autonomous elliptic tops. Finally, it is mentioned that the matrix valued variables can be replaced by elements of noncommutative associative algebra. At the end of the paper we also describe special elliptic Gaudin models which can be considered as matrix extensions of the ( Z 2 reduced) elliptic top.